Developing Reading Learning Model to Increase Reading Skill for Animal Husbandry Students in Higher Education - Abd. Syakur; Rosidi Azis; Sukarsih (Britain International for Academic Research (BIAR) Publisher, 2020)
The development of teaching and learning activities must be evaluated to find out the success or failure of learning. This evaluation must be done because teaching now will certainly affect the next learning process, especially the reading comprehension model. This study aims to produce a reading comprehension model that is able to improve the reading comprehension skills of second semester students in the English for Professions subject to 2 Semester Credit Systems (SKS) in the department of animal husbandry at the University of Nahdlatul Ulama Blitar. The study approach used was Research and Development by modifying the ten steps of implementing the research strategy into three steps. The research subjects were lecturers and students majoring in animal husbandry at the University of Nahdlatul Ulama Blitar. Data collection techniques used was observation, questionnaires, interviews and tests. Research data analyzed using qualitative and quantitative analysis techniques. Data results show that the use of reciprocal teaching reading strategies combined with peer-teaching methods can significantly improve students' reading comprehension skills. The care giving effect arising from the application of reciprocal teaching to reading comprehension increases social values in second semester students in the English for Professional course.